Analysis of Consumer Preferences to the Quality of Street Vendor Coffee in Payakumbuh City - Silfia Silfia; Pinta Aftaprilia Rizki Ananda Ananda; Reza Mardhiyah Amir; Maulia Usni; Walmadri Walmadri (Andalasian International Journal of Agriculture and Natural Sciences (AIJANS), 2026)
This study aims to analyze consumer preferences to the quality of street-vendor coffee in payakumbuh city and identify the factors influencing consumer purchasing decisions. The method used is a quantitative approach. 100 street-vendor coffee consumers selected using purposive sampling method. Data were collected through questionnaires, observations, and documentation, then analyzed using Spearman’s Rank Correlation Analysis. The results showed that the price perception factor has the strongest and most significant relationship with purchasing decisions (rs = 0.727) and followed by product quality (rs = 0.512). These findings suggest that affordability, perceived price fairness, consistent taste, safety, and practical packaging are key determinants shaping consumer preferences and encouraging repeat purchases. The demographic characteristics of respondents dominated by young consumers with low to middle income further emphasize the importance of competitive pricing in this market segment. This findings implicate that street-vendor coffee business operators need to implement competitive pricing strategies while maintaining consistent product quality, particularly in terms of taste, safety, and practical packaging, in order to enhance perceived value and encourage purchases. Local governments should design empowerment programs for street-vendor coffee MSMEs, including food hygiene training, product quality improvement, and market-oriented business management.